The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1080/1028415x.2017.1347998
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient composition of a morning meal and the maintenance of attention throughout the morning

Abstract: Background At present, the impact of macronutrient composition and nutrient intake on sustained attention in adults is unclear, although some prior work suggests that nutritive interventions that engender slow, steady glucose availability support sustained attention after consumption. A separate line of evidence suggests that nutrient consumption may alter electroencephalographic markers of neurophysiological activity, including neural oscillations in the alpha-band (8–14 Hz), which are known to be richly inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…Participants performed the visual Continuous Temporal Expectancy Task (vCTET), which was adapted from one previously used by O’Connell et al (2009) and Berry, Li, Lin, and Lustig (2014). It was chosen because of its prior use in sustained attention research (Berry et al, 2014; Wilson, Gray, Van Klinken, Kaczmarczyk, & Foxe, 2017), and because of the finding that errors on this task are preceded by significant increases in EEG alpha power (Dockree et al, 2017; O’Connell et al, 2009). This latter finding indicates a negative association between vCTET performance and alpha activity, motivating our prediction that alpha-tACS would impair performance on this task.…”
Section: Methodsmentioning
confidence: 99%
“…Participants performed the visual Continuous Temporal Expectancy Task (vCTET), which was adapted from one previously used by O’Connell et al (2009) and Berry, Li, Lin, and Lustig (2014). It was chosen because of its prior use in sustained attention research (Berry et al, 2014; Wilson, Gray, Van Klinken, Kaczmarczyk, & Foxe, 2017), and because of the finding that errors on this task are preceded by significant increases in EEG alpha power (Dockree et al, 2017; O’Connell et al, 2009). This latter finding indicates a negative association between vCTET performance and alpha activity, motivating our prediction that alpha-tACS would impair performance on this task.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects covertly attend one of two rotating checkerboard streams and report the appearance of duration deviants (targets) that appear as pauses or breaks in the rotation rhythm. We will here describe the task, but the reader is encouraged to review our recent publications for additional descriptions of the task and characterization of associated neurophysiological findings (Gray, Frey et al 2015, Wilson, Gray et al 2018.…”
Section: Stimuli Task and Experimental Protocolmentioning
confidence: 99%
“…Average hit rates across experimental session were: 66% (Day 1; σ = ±14%); 64% (Day 2; σ = ±17%); and 65% (Day 3; σ = ±17%). For additional behavioral analysis by experimental session, see Wilson, Gray et al (2018; especially Figure 3). As shown in Figure 5, Top Left, average reaction times (in ms) for each condition were: Left (1.5 Hz): 610 (σ = ±90); Left (1.3 Hz): 610 (σ = ±100); Right (1.5 Hz): 630 (σ = ±90); Right (1.3 Hz): 620 (σ = ±90).…”
Section: Frontal Delta Phase Correlates With Behaviormentioning
confidence: 99%
“…Some studies of children and adolescents showed that the intake of breakfast with more energy has positive effects on short-term memory [8,9]. Other studies of adults mainly focused on the effects of glycemic index (GI), macronutrients, and micronutrients in breakfast on cognitive function [10][11][12][13][14][15][16]. They found that a high GI breakfast is more bene cial for cognitive function compared with a low GI breakfast [10][11][12][13] and a breakfast drink of high carbohydrate or protein may improve coping with mental tasks, including working memory and attention [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of adults mainly focused on the effects of glycemic index (GI), macronutrients, and micronutrients in breakfast on cognitive function [10][11][12][13][14][15][16]. They found that a high GI breakfast is more bene cial for cognitive function compared with a low GI breakfast [10][11][12][13] and a breakfast drink of high carbohydrate or protein may improve coping with mental tasks, including working memory and attention [14][15][16]. However, several studies showed contradictory results that a low GI breakfast or skipping breakfast is more bene cial for adults' cognitive function [16][17][18].…”
Section: Introductionmentioning
confidence: 99%